Trends in Tourism Entrepreneurship Research: A Systematic Review - Alhammad, Fawwaz (Jordan Journal of Business Administration, 2020)
The importance of entrepreneurship for tourism and local community involvement in tourism activities have been recognized by both researchers and practitioners. This article aims at identifying the state of academic research on tourism entrepreneurship and identifying what should be done in the development of the entrepreneurship theories in the tourism field. The research presents a systematic review of tourism entrepreneurship literature following a procedure used in previous studies (i.e., Torraco, 2005; Tafesse and Skallerud, 2017). The findings revealed that tourism entrepreneurship articles significantly increased after 2016. The study offered a synthesis of research findings and provided a discussion and proposals for future research agenda.